RELEVANSI DAN APLIKASI ALIRAN EKONOMI KELEMBAGAAN - Santosa, Purbayu Budi (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2008)
School of institutional economics emerged as rampant reaction of education and usage of neoclassic economics in research and policy application at most developed and developing countries. The school in developed countries gets many criticisms, also in developing countries that having difference in condition of economics area, social, politics, law, and culture. Usage of qualitative and quantitative research method can be utilized because of approach of the method which holistic. Usage of institutional economics school in education, research, and policymaking, appropriate in Indonesia with economics problem complexity.